Conversor CC-CC trifásico isolado bidirecional LLC ressonante utilizando uma técnica de controle por deslocamento de fase e modulação em frequência - Santos, Kristian Pessoa dos (2020)
This work presents a theoretical study and design of an novel proposed of an isolated threephase DC-DC bidirectional LLC resonant converter using a technique of phase shift control and frequency modulation. For the mathematical analysis of the converter, a single-phase model was used considering only the fundamental components. In addition, all switches, diodes, inductors, capacitors and transformers were considered ideal. The converter resonant circuit has the advantage to take the dispersion inductances of high frequency transformer and its magnetizing inductance to compose the resonant circuit that significantly improves its power density. The study of the dynamic behavior of the converter considering that the semiconductor switches are always with 50% duty cycle is developed so that for the converter to always operate with ZVS switching, several switching frequency variation and load changes are analyzed. Thus, one of the contributions of this work is that in addition to the phase parallelism already present in the structure, high efficiency can be obtained for each power range with frequency control, always keeping it within the smooth switching zone. ZVS switching allows the effects caused by EMI to be reduced. The dynamic converter model is obtained through the gyrator theory, where the circuit can be modeled as a frequency-controlled current source to control the output voltage of the converter. In addition, the direction of the converter's power flow is determined by the estimation of an ideal phase-shift angle for each switching frequency point to obtain the output power of the converter. An example project of 1,5 kW is calculated and developed with output voltage equal to 380V. Experimental results are presented and discussed to validate the proposed converter. Smooth switching over a wide load range and maximum efficiency of approximately 95% was achieved. It can be used for the integration between the battery system and the high voltage DC bus of hybrid and electric vehicles.